Nanoporous carbon superstructures based on covalent bonding of porous fullerenes - Silveira, Julian F.R.V.; Pagnussati, Rafaela A.; Kleinpaul, Júlia; Paupitz, Ricardo [UNESP]; Muniz, Andre R. (Elsevier, 2018)
Highly porous and mechanically stable nanostructures are of great interest for applications in selective membranes, adsorbents, catalysts and sensors. In this study, we use Density Functional Theory calculations and Molecular Dynamics (MD) simulations to demonstrate the feasibility of a novel class of porous carbon-based nanostructures with uniform pore size distributions, formed by covalent bonding of porous fullerenes. Their corresponding mechanical and electronic properties are evaluated, and results show that they typically exhibit an outstanding mechanical strength and electronic behavior ranging from metallic to semiconducting, depending on the hybridization of the covalent interconnections and dimensionality. The efficacy of these materials as molecular sieves is also demonstrated using MD simulations of gas transport across the nanoporous structure. This combination of properties makes these nanostructures suitable for the development of novel porous functional materials with several potential applications.